Detecting SARS-CoV-2 3CLpro expression and activity using a polyclonal antiserum and a luciferase-based biosensor - O'Brien, Amornrat; Chen, Da-Yuan; Hackbart, Matthew; Close, Brianna J.; O'Brien, Timothy E.; Saeed, Mohsan; Baker, Susan C. (Virology (New York, N.Y.), 2021)
The need to stem the current outbreak of SARS-CoV-2 responsible for COVID-19 is driving the search for inhibitors that will block coronavirus replication and pathogenesis. The coronavirus 3C-like protease (3CLpro) encoded in the replicase polyprotein is an attractive target for antiviral drug development because protease activity is required for generating a functional replication complex. Reagents that can be used to screen for protease inhibitors and for identifying the replicase products of SARS-CoV-2 are urgently needed. Here we describe a luminescence-based biosensor assay for evaluating small molecule inhibitors of SARS-CoV-2 3CLpro/main protease. We also document that a polyclonal rabbit antiserum developed against SARS-CoV 3CLpro cross reacts with the highly conserved 3CLpro of SARS-CoV-2. These reagents will facilitate the pre-clinical evaluation of SARS-CoV-2 protease inhibitors. •Coronavirus 3CLpro activity is efficiently measured using a luciferase-based biosensor.•Small molecule inhibitors of 3CLpro block activation of the biosensor.•Polyclonal antiserum raised against SARS-CoV 3CLpro recognizes SARS-CoV-2 3CLpro in WB and IF assays.